Application of microwave heating in polymer synthesis: A review - Emranul Kabir (Results in Chemistry, 2023)
Microwave (MW) heating has developed rapidly and it is currently utilized in a variety of industries, especially in the manufacturing of materials. The heating mode of MW offers a good substitute for conventional heating by consuming less time and energy, which reduces the cost and ecological effect of polymer chemistry and processing. Recently, utilization of microwave radiation (MWR) in polymer research has been established as a reliable method to encourage and enhance chemical reactions. The prime benefits of microwave heating comprise a significant decrease in reaction time and a great potential for sustainable chemistry. The use of microwaves as an energy source during the synthesis as well as the transformation of polymers has made some improvements, as stated in this review. Current examples of microwave-assisted polymerization are reviewed in brief, with a particular emphasis on ring opening polymerization, controlled radical polymerization, click chemistry polymerization, organic–inorganic polymer hybrids, polyesters and polyamides, metal catalyzed cross coupling polymerization, polymer nanocomposite materials, biodegradable and bioactive polymer composite, semiconducting polymerization, graphene-based polymer composite materials.